2019
DOI: 10.3390/foods8020063
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Solanum nigrum L. Leaf Extracts Determined in In Vitro Cellular Models

Abstract: Several medicinal foods abound in traditional medicine with antioxidant potentials that could be of importance for the management of several diseases but with little or no scientific justification to substantiate their use. Thus, the objective of this study was the assessment of the antioxidant effect of two leave extracts of Solanum nigrum L. (SN), which is a medicinal plant member of the Solanaceae family, mainly used for soup preparation in different parts of the world. Then methanolic/water (80:20) (SN1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…S. nigrum L., bitter and sweet in flavor, slightly cold in property, acting on the lung and urinary bladder channels with the effects of clearing away heat, removing toxicity, detumescence, and relieving itching, mainly treating carbuncle, eczema, and dermatitis. S. nigrum L. is wildly used in TCM for the treatment of a wide range of diseases including some eye infections, seizure, epilepsy, inflammation, pain, diarrhea, ulcer, and jaundice (Campisi et al, 2019). T. mongolicum Hand.-Mazz, bitter and sweet in flavor, cold in property, acting on the liver and stomach channels with the effects of clearing away heat, removing toxicity, reducing swelling, and dissipating mass.…”
Section: Discussionmentioning
confidence: 99%
“…S. nigrum L., bitter and sweet in flavor, slightly cold in property, acting on the lung and urinary bladder channels with the effects of clearing away heat, removing toxicity, detumescence, and relieving itching, mainly treating carbuncle, eczema, and dermatitis. S. nigrum L. is wildly used in TCM for the treatment of a wide range of diseases including some eye infections, seizure, epilepsy, inflammation, pain, diarrhea, ulcer, and jaundice (Campisi et al, 2019). T. mongolicum Hand.-Mazz, bitter and sweet in flavor, cold in property, acting on the liver and stomach channels with the effects of clearing away heat, removing toxicity, reducing swelling, and dissipating mass.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant properties of medicinal plants play an important role in Ayurvedic treatments due to their multifaceted action. The significant positive correlation between phenols, flavonoids with different antioxidant assays such as DPPH, RP, and CUPRAC indicated that these bioactive compounds play a role in the antioxidant property of the plant 32,33 . Earlier reports suggested that phenolic compounds concentrated in the fruit skin contribute to their antioxidant property.…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegeneration is supposed to be potentiated with uncontrolled production of free radicals which can be controlled up to some extent with external antioxidants. Inabussalab (Solanum nigrum Linn) is reported to have significant antioxidant and anti-inflammatory activities [45][46][47] . Anti-inflammatory action of Beikh-e-Kibr (Capparis spinosa Linn) has been proved in various reports.…”
Section: Sudadmentioning
confidence: 99%